Continuity and change in Israeli security policy - Heller, Mark.; International Institute for Strategic Studies (Oxford ; New York : Oxford University Press for the International Institute for Strategic Studies, 2000)
This paper examines the foundations of Israeli security policy and analyses the impact of changes in the external threat environment and in domestic politics and society. It argues that the traditional policy of deterrence based on "offensive defence," elaborated under David Ben-Gurion and his successors, is no longer adequate in the face of the new challenges posed by low-intensity warfare and weapons of mass destruction. Israel's ability to meet these challenges depends to a large extent on the fate of the peace process. This in turn hinges, at least in part, on the outcome of the domestic contest over the future character of Israeli politics and society. This contest is essentially between two positions: one inward-looking or "backlash," the other outward-looking or "internationalist." Its outcome will have long-term implications for Israel's security policy, both in terms of the kinds of threats that the country will face, and how well it will be able to deal with them.
The traditional security concept -- The evolution of the threat after 1967 -- Internal challenges -- Adapting defence policy -- Alternative futures -- Towards "limited internationalism"?
Includes bibliographical references (pages 77-84).
Keywords: Israel; Since 1993; National security -- Israel; Israel -- Defenses; Israel -- Foreign relations; Israel -- Military policy; Israel -- Politics and government -- 1993-; Israel; Israel -- Military policy; Political science; Book